Piper betle L. and Psidium guajava L. in oral health maintenance - Fathilah, A.R. (2011)
The objective of the study was to seek for new agents from plant extracts for use in dental plaque control. The emphasis was directed at the initial stage of dental plaque formation, specifically the adherence of bacteria referred to as the early plaque colonisers, to the acquired pellicle on the supragingival tooth surface. Streptococcus sanguinis, Streptococcus mitis and Actinomyces sp., the predominant bacteria involved at this initial stage of plaque development were used as test organisms. The aqueous extracts of Piper betle and Psidium guajava exhibited antimicrobial activities with MIC values in the range of 2.61 to 4.69 mg/mL and toxicity values (LC(50) and EC(50)) well above their toxic concentrations. P. betle and P. guajava extracts contained 9.25 and 11.5 ppm fluoride, respectively. Some aggregating activity was also displayed by the extract of the latter. Both extracts showed positive antiadherence activity and reduced the cell-surface hydrophobicity of the bacteria which might have rendered them less adherent and hence, minimising their adhesion to the tooth surface during the early stage of plaque development. Both extracts also suppressed the growth of these bacteria. Such an activity was reaffirmed and supported by SEM micrographs whereby the bacterial cells were unable to divide or grow successfully and hence suggesting bacteriostatic effect of the extracts. Extracts of P. betle and P. guajava may work by first preventing and reducing the adhesion of primary bacterial colonisers to the tooth surface and second, to prevent or inhibit the growth and proliferation of microorganisms adhering on to the tooth surface and may potentiate their antiplaque activities.